THE INFLUENCE OF ENVIRONMENTAL CONDITIONS ON SEASONAL CYCLES OF DEVELOPMENT OF THE LEUCOJUM AESTIVUM, GALANTHUS WORONOWII AND PANCRATIUM MARITIMUM - N. A. Slepchenko (Юг России: экология, развитие, 2014)
Ecological conditions of habitats essentially influence on phenological phases terms at Leucojum aestivum, Galanthus woronowii and Pancratium maritimum on the Black Sea coast ofRussia. The general duration of vegetation of Leucojum aestivum and Galanthus woronowii populations on the shaded habitats exceeds that for the opened habitats on 3 and 2 weeks respectively; Pancratium maritimum, on the contrary, differs continuous vegetation on open habitats. Despite earlier beginning of flowering in the shaded conditions, fruits maturing of Leucojum aestivum and Galanthus woronowii is noted for a week later, than on the shined habitats; flowering of Pancratium maritimum in the shaded conditions can not be observed.